Left or right, who is more pseudoscientific? An analysis of the pseudoscientific beliefs of students on the Psychology course at Feevale University - Schmidt, Rodrigo (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2024)
The university's mission is to safeguard and preserve knowledge, yet even in this intellectually elitist environment, pseudoscience prevails. This concept, often sensationalized in contemporary media and ridiculed by those whose beliefs are labeled pseudoscientific, trivializes science. This leads to increased adherence to and utilization of these concepts, particularly in health contexts or academia. This article aims to assess the persistence of pseudoscientific beliefs among students in this ostensibly sacred knowledge sanctuary. Instruments measuring belief in pseudoscientific concepts and their ramifications were employed. Additionally, the group was evaluated regarding their political stance and adoption of psychological currents, including CBT and Psychoanalysis. The latter, despite being classified as non-scientific, persists in the Brazilian educational structure.